Morphology and histology of the digestive system of raspberry weevil Aegorhinus superciliosus (Coleoptera: Curculionidae) - Medel, Vivian; Molina, Benedicto; Seguel, Jorge; Rebolledo, Ramón; Quiroz, Andrés (Revista Colombiana de Entomología, 2013)
A morphological and histological study was performed on the digestive system of Aegorhinus superciliosus (Coleoptera: Curculionidae), an important economic pest in southern Chile. This species has a typical digestive system for most insects, being similar in males and females, but longer in the latter, being twice the length of the insect. The digestive system is a long tube of variable diameter, divided into three regions: foregut, midgut and hindgut. From the histological point of view, it presents epithelium tissue features similar to the one described for other species, and externally it has a muscle tissue with no differences between males and females. Nevertheless, it shows features which differ either in other weevils or in beetles such as: absence of crop, the location and number of gastric caeca, presence of peritrophic membrane, and absence of a rectal pad.